Polyphenol capping on a gold nanosurface modulates human serum albumin fibrillation. Issue 5 (6th July 2020) - Basu, Aalok; Kundu, Sonia; Das, Aatrayee; Basu, Chitra; Bhayye, Sagar; Das, Suvadra; Mukherjee, Arup
Abstract : The antioxidant capacity inherent to polyphenol-capped gold nanoparticles contributed to the inhibition of human serum albumin fibrillation. Abstract : Different small molecules and nanomaterials have been known as inhibitors of protein misfolding and subsequent fibrillation, which marks the initiation of various degenerative conditions. This work explores the effect of polyphenol-capped gold nanoparticles on the extent of human serum albumin fibrillation. Silymarin-capped (SAuNPs), quercetin-capped (QAuNPs) and gallic acid-capped gold nanoparticles (GAuNPs) were synthesized with a uniform size range and their relative antioxidant capacity was determined through DPPH assay. The fibrillation of HSA at 65 °C was inhibited by ∼15% in the presence of SAuNPs and the process was monitored through a combination of Thioflavin T fluorescence spectroscopy, circular dichroism spectroscopy and microscopic analysis. The inhibitory effect appeared much pronounced in the case of QAuNPs (∼67%) and GAuNPs (∼60%). Using SDS PAGE analysis, we demonstrated that the different inhibitory activity of SAuNPs, QAuNPs, and GAuNPs could be attributed to the antioxidant potential of the individual nanoparticles. Our work revealed that apart from protein–nanoparticle surface interactions, the antioxidant capacity has a role in determining the effectiveness of a protein fibrillation inhibitor. Cytotoxic analysis of protein–gold nanoparticle aggregates on HaCaT cell lines further confirmed that the nanoparticles were biosafe and can be considered as active therapeutics for translational use.